Differentiation in education: a configurative review - Ingunn Eikeland; Stein Erik Ohna (Taylor & Francis Group, 2022)
Differentiation in education can be seen as a means of responding to student diversity in order to meet the vision of a school for all. Differentiation has been widely addressed within a western context, and it appears to be a versatile phenomenon as it occurs under various guises and with a variety of terms and modes of operationalizations. The aim of this configurative review is to investigate how differentiation appears in the international context and to contribute to a much-needed overview of the concept. Analysis of 28 scientific papers representing a broad range of national affiliations resulted in two main findings. First, differentiation is a complex idea that appears to be presented either as differentiating students or differentiating teaching. Four perspectives for approaching differentiation further illustrate the complexity of the phenomenon: differentiation as individualization, differentiation as adaptation to specific groups, differentiation as adaptations within diverse classrooms, and differentiation in a system perspective. Second, the analysis revealed that there are almost no studies transcending the focus on teachers and the classroom by addressing the organizational or system/policy level. This review argues for the benefits that a more system-oriented perspective of differentiation would provide.